Preferences for tongue swab-based versus sputum-based testing in the context of TB care: a best-worst scaling exercise in Vietnam and Zambia - Castro, María del Mar; Le, Hien; Muzazu, Seke; Pham, Nam; Trang Trinh; Nyirenda, Herbert Chabwera; Shabalu, Patricia; West, Nora; Phan, Ha; Cattamanchi, Adithya; Denkinger, Claudia M.; Muyoyeta, Monde; et al. (BMJ global health, 2025)
Background The development of non-sputum-based tests is an urgent priority to increase access to tuberculosis (TB) diagnostic testing. Understanding preferences of people undergoing testing is critical for designing tests and strategies aligned with their needs.Methods We conducted a survey and best-worst scaling (BWS) exercise to determine relative preferences for tongue swab-based versus sputum-based testing among people (≥13 years) with presumptive TB at primary health centres in Vietnam and Zambia. The BWS assessed 16 TB test features, including accuracy, sample type, turnaround time, cost and service aspects. We estimated mean rescaled preference weights, our primary outcome, using Hierarchical Bayes modelling and identified distinct preference groups using latent class multinomial logit analyses (LCA).Results Among 409 participants enrolled, 356 (87%) met quality criteria for analysis. The median age of participants was 39 years (IQR 29-47), and most were female (60.7%). When asked directly, most participants preferred providing tongue swabs over sputum (58.1% vs 28.7%, p<0.001; 12.4% no preference). In the BWS exercise, tongue swab was also preferred over sputum (mean rescaled preference weights (MPWs) 6.4, 95% CI 5.9 to 6.8 vs 5.0 95% CI 4.6 to 5.4). However, support and counselling (MPW=14.0), sensitivity (MPW=12.3), specificity (MPW=10.2) and provider attitude (MPW=7.4) were the most important features overall. Less important features included facility opening hours (MPW=3.4) and the influence of trusted sources on testing decisions (MPW=2.2). LCA identified five distinct preference groups, but support and counselling were universally valued. Participants in Groups 2 (27.3%; n=97) and 3 (17.1%; n=61) valued tongue swabs over many other features. Group 5 participants (11%; n=39) strongly valued sputum-based testing.Conclusions Participants in Vietnam and Zambia preferred tongue swab-based TB testing over sputum. However, sample type was less important than test accuracy and other TB care features affecting the testing experience.
Gesehen am 10.02.2026